Modern management of phagocyte defects. Issue 2 (13th October 2016) - Lanini, Lorenza Lisa Serena; Prader, Seraina; Siler, Ulrich; Reichenbach, Janine
Abstract: Phagocytic neutrophil granulocytes are among the first immune cells active at sites of infection, forming an important first‐line defense against invading microorganisms. Congenital immune defects concerning these phagocytes may be due to reduced neutrophil numbers or function. Management of affected patients depends on the type and severity of disease. Here, we provide an overview of causes and treatment of diseases associated with congenital neutropenia, as well as defects of the phagocytic respiratory burst.